2019
DOI: 10.15832/ankutbd.441916
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Barley Landraces and Wild Barley (Hordeum spontaneum) Genotypes Resistant to Rhynchosporium commune

Abstract: Barley scald is caused by the fungal pathogen Rhynchosporium commune. This disease causes substantial losses in barley production areas of the world. In this study, seedling resistance of 198 barley landraces, 104 wild barley (Hordeum spontaneum) genotypes and two susceptible Turkish cultivars (Bülbül 89 and Efes 3) to 6 R. commune isolates was assessed in greenhouse experiments. Virulence differences among the R. commune isolates were observed. One sixrowed barley landrace (Yeşilköy 9052) was resistant to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
(17 reference statements)
3
7
0
Order By: Relevance
“…Based on disease scoring, it has been observed that six-row Turkish barley varieties had lower reaction values to R. commune compared to those of two-row varieties. This finding is correlated with the results obtained in various studies [11,18,19,32,33]. In addition, Albustan et al [34] determined that only the variety Erginel 90 was determined resistant to R. commune among the 15 barley varieties tested in reaction studies conducted in both field and greenhouse conditions.…”
Section: Discussionsupporting
confidence: 82%
“…Based on disease scoring, it has been observed that six-row Turkish barley varieties had lower reaction values to R. commune compared to those of two-row varieties. This finding is correlated with the results obtained in various studies [11,18,19,32,33]. In addition, Albustan et al [34] determined that only the variety Erginel 90 was determined resistant to R. commune among the 15 barley varieties tested in reaction studies conducted in both field and greenhouse conditions.…”
Section: Discussionsupporting
confidence: 82%
“…Among the barley differential cultivars, Jet and Abyssinia showed the most resistant reactions to R. commune and these two differential cultivars may be used as genitors in future barley scald resistance breeding programs. Also, wild barley (Hordeum spontaneum) and barley landraces can be used in scald resistance breeding studies (Azamparsa et al 2019). For better management of the disease, information about the pathotype composition of fungus is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Four isolates were the most virulent isolates (GPS71-U, 13GPS203, 13GPS207, and 13GPS109) in the study of Azamparsa and Karakaya (2020). Whereas, one isolate was the most virulent (13GPS149) and another represented the most common pathotype (E4) from Azamparsa et al (2019). Isolates GPS71-U, 13GPS203, 13GPS207, 13GPS109, 13GPS149 and E4 were obtained from the Gaziantep-Subağı, Manisa-Kula, İzmir-Bergama, Ankara-Şere ikoçhisar, Mardin-Midyat and Eskişehir-Tepebaşı regions of Turkey, respectively.…”
Section: Biological Materialsmentioning
confidence: 99%
“…Following inoculation, plants were transferred to a mist chamber with 100% relative humidity at 16-17°C for 48 hours. Two days post inoculation, plants were moved to the greenhouse with a 20-25°C temperature range (Azamparsa et al 2019). The disease assessment was made using a 0-4 scale developed by El-Ahmed (1981) 18 days post inoculation and used in subsequent association mapping.…”
Section: Phenotypic Assaymentioning
confidence: 99%
See 1 more Smart Citation